Optimal HEVC Configuration for Wireless Video Communication Under Energy Constraints - Milad Abdollahzadeh; Hadi Seyedarabi; Javad Musevi Niya; Ngai-Man Cheung (IEEE Access, 2018)
High Efficiency Video Coding (HEVC) provides a doubling in coding efficiency compared with the H.264/AVC at the expense of increased computational complexity. However, mobile devices that perform video encoding and communication over wireless networks have limited energy supply. A video encoding system which has the ability to adjust its computational complexity and power consumption could be used to prolong the lifetime of these devices. In this paper, we develop a framework, which selects the optimal HEVC encoding configuration in order to optimize the performance of the wireless video communication system under energy constraints. More specifically, in this paper, we develop an analytic HEVC encoder behavior model based on the extensive analysis of key HEVC encoding tools. We use the developed model for the performance optimization of the HEVC encoder under energy constraints. We propose an adaptive algorithm to estimate the HEVC encoder model parameters and perform online encoder coding configuration optimization. We show that using the proposed framework, the video encoder is able to select appropriate coding tools to automatically adjust its coding efficiency and complexity to match the available power budget with the maximum possible video quality. The proposed HEVC encoder model provides a guideline for optimized tool selection in the energy constrained wireless video communication.